Adsorption Kinetics and Isotherms of Cr(VI) Ions in Aqueous Solution by Biochar Derived from Torreya grandis Nutshell - Chengcai Huang, Rui Qin, Linli Zhang, Muqing Qiu and Linfa Bao (Nature Environment and Pollution Technology, 2019)
Biochar is thought to be a good adsorption material for the adsorption of heavy metals. In this study, biochar derived from Torreya grandis nutshell was prepared through to be pyrolyzed under oxygen limited conditions in a muffle furnace. The adsorption experiments of Cr(VI) were carried out. Through Elemental Analyzer, Specific Surface Area Meter, Scanning Electron Microscopy, Transmission Electron Microscopy and Fourier Transform Infrared Spectroscopy, a fundamental understanding of the physical and chemical properties of biochar was gained. The results showed that it was a smooth sheet and irregular arrangement structure. The elements of C, H, O and N of biochar are 45.21%, 5.18%, 46.16% and 3.45% respectively. BET specific surface area of biochar is 42.24 m2/g. A lot of oxygencontaining functional groups (– OH, COO –, – C – OH and so on ) appeared on the surface of biochar. It can be described by the pseudo-second order kinetic rate model and Langmuir isotherm model. The adsorption process is a monolayer chemical process. The adsorption mechanism of biochar on heavy metal Cr(VI) contains the electrostatic attraction between biochar and Cr2O7 2-, HCrO4 - and CrO4 2- ions in aqueous solution and complexation reaction of oxygen-containing functional groups (– OH, – COOH and so on) and Cr2O7 2- , HCrO4 - and CrO4 2- ions on the surface of biochar.